Estabelecimento de espécies arbóreas nativas por semeadura direta em área de restauração florestal na Mata Atlântica - Tangerina, Lucas Panisa (Universidade Federal de São Carlos, 2026)
Direct seeding forest restoration has been considered an alternative to scale up ecological restoration, but its success depends on the establishment, growth, and persistence of species in the field. This study aimed to evaluate the establishment, growth, and structural and functional contribution of native tree species in a forest restoration area using direct seeding, located at the Center for Agricultural Sciences of the Federal University of São Carlos, in Araras, SP, six years after implementation. The experimental area consists of 0.27 ha and was originally planted with 29 native tree species, in a design composed of six blocks and four treatments. Established tree individuals were evaluated, with records of species, height, diameter, and experimental position. From the collected data, indicators of establishment, density, growth, basal area, biomass, carbon, and costs associated with direct seeding were calculated. At 72 months after implementation, 5,219 established individuals were recorded, distributed across 13 species. Sapindus saponaria showed the highest number of individuals, higher density, and greater linear occupation, while Peltophorum dubium showed greater structural growth, average biomass per individual, and total estimated carbon per species. For carbon estimates, 1,526 individuals with D30 greater than 3 cm were considered, according to the criterion adopted for inclusion in the calculations. On an aggregate scale, the area presented an estimated density of 19,329.63 individuals ha⁻¹, a carbon stock of 44.06 Mg C ha⁻¹, an average cost of R$ 0.62 per established individual, and a total implementation cost of R$ 12,060.54 ha⁻¹. The results demonstrate that direct seeding was efficient in forming an established tree community, albeit with selective performance among species. It is concluded that the evaluation of direct seeding must integrate indicators of establishment, growth, biomass, carbon, and cost, allowing the identification of species with different forms of contribution to forest restoration.
Establishment of native tree species by direct seeding in an Atlantic Forest restoration area
Keywords: Restauração ecológica; Sementes nativas; Estabelecimento de espécies; Biomassa; Carbono; Ecological restoration; Native seeds; Species establishment; Biomass; Carbon; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; 15. Vida Terrestre; 13. Ação contra a Mudança Global do Clima